Length of hospital stay after delivery among Danish women with congenital heart disease: a register-based cohort study - Anne Marie Kirkegaard; Maria Breckling; Dorte Guldbrand Nielsen; Janne S. Tolstrup; Søren Paaske Johnsen; Annette Kjær Ersbøll; Stine Kloster (BMC, 2021)
Abstract Background The literature about the impact of congenital heart disease (CHD) on the length of hospital stay after delivery is limited, and nonexisting in a country with free and equal access to healthcare. We aimed to examine the hypothesis that Danish women with CHD have a longer hospital stay after delivery compared to women without CHD. Secondarily, we aimed to examine the hypothesis that cesarean section modifies the association. Methods The study was a national cohort study using Danish nationwide registers in 1997-2014. Maternal CHD was categorized as simple, moderate, or complex CHD. The comparison group consisted of women without CHD. Outcome of interest was length of hospital stay after delivery registered in complete days. Mode of delivery was categorized as cesarean section or vaginal delivery. Data was analyzed using a generalized linear model with a Poisson distribution. Results We included 939,678 births among 551,119 women. Women without CHD were on average admitted to the hospital for 3.6 (SD 3.7) days, whereas women with simple, moderate, and complex CHD were admitted for 3.9 (SD 4.4), 4.0 (SD 3.8) and 5.1 (SD 6.7) days, respectively. The adjusted length of hospital stay after delivery was 12% (relative ratio (RR) = 1.12, 95% confidence interval (CI) 1.07-1.18), 14% (RR = 1.14, 95% CI: 1.07-1.21), and 45% (RR = 1.45, 95% CI: 1.24-1.70) longer among women with simple, moderate, and complex CHD, respectively, compared to women without CHD. The association between maternal CHD and length of hospital stay was not modified by mode of delivery (p-value of interaction = 0.62). Women who gave birth by cesarean section were on average admitted to the hospital for 2.7 days longer compared to women with vaginal delivery. Conclusion The hospital stay after delivery was significantly longer among women with CHD as compared to women without CHD. Further, higher complexity of CHD was associated with longer length of stay. Cesarean section did not modify the association.